Youth Activism for Climate on and Beyond Social media: Insights from FridaysForFuture-Rome. (July 2022) - Belotti, Francesca; Donato, Stellamarina; Bussoletti, Arianna; Comunello, Francesca
The FridaysForFuture movement (FFF), launched by Greta Thumberg's school strikes in 2018, has led a new wave of climate activism worldwide. Young people are at the forefront, with social media serving both as mobilizing tools and expressive spaces. Drawing upon literature on youth and digital activism with a generational, situated approach, we account for how both the climate struggle and social media are appropriated by FFF-activists as part of their own youth grassroots politics. Moreover, we explore the activities they mix and the strategies they adopt when moving across online and offline environments. From July 2020 to January 2021, we carried out 6 months of ethnographic work with(in) the FFF-Rome group by blending participant observation of assemblies and protests with digital ethnography on the homonym WhatsApp group. Results' thematic analysis shows that FFF-activists believe climate activism to be their own fight and social media their own battlefield. A generational understanding of digital climate activism emerges at the intersection of the appropriation of the dispute (climate change) and the digital environments (social media). Findings also account for broader logics and strategies adopted by FFF-activists, on and beyond social media. They move seamlessly between online and offline, spanning across and negotiating with different platforms according to political goals and target audiences. These results contribute to overcoming reductive or marginalizing approaches to youth activism, to legitimizing and situating young activists' social media usage practices within an array of grassroots political practices, and to understanding how generational belonging affects such practices in the Italian context.